Mumarasat al-siyasah al-shar'iyah 'inda al-aqaliyat al-Muslimah : Majlis al-'Alaqat al-Islamiyah al-Amarikiyah namudhajan = The practice of siasah syar'iyyah among Muslim minority : a case study of the Council on American-Islamic Relations / Bahaeddine Megaache - Megaache, Bahaeddine (2010)
This research aims to uncover the reality of the Muslim minority in the United States of America, and the position of the Council on American-Islamic Relations (CAIR), and how to deal with emerging issues of Muslims there. For instance, participation of the American Muslim in the United States military service as well as his participation in elections. The researcher has represented the opinions and views of some contemporary scientists about this kind of issues. The researcher relies on the principles of the inductive and descriptive method, and he used the analytical machinery in dealing with the available in formation on this subject by returning to the most recent studies that have been established on “muslim minorities”, as well as through the interview contucted with the Dr.: Nihad Awad, Chairman of the Council on American-Islamic Relations (CAIR). As such, the study has given a critical evaluation to this experience and its prospects as well as choose what is accurate according the deductive force within the objectives of Islamic law purposes (Maqasid Al Shari’ah). The research has ended to an inevitable result which says that working within the sending benefit is the best and appropriate solution to deal with this kind of issues and communicating with others.